Why do young men lapse from blood donation?. Issue 6 (23rd May 2019) - Öhrner, Caroline; Kvist, Maria; Blom Wiberg, Karolina; Diedrich, Beatrice
Abstract : Background and Objectives: Most men have larger blood volumes and iron stores, making them more suitable blood donors; however, women dominate the donor population in Stockholm. Motives for cessation and returning were examined in a group of lapsing young male donors, in order to improve retention. Methods: Demographic studies of the donor population. An online survey was sent to 1012 lapsing male donors aged 18–35 years. Questions focused on reasons for lapsing, returning and donor motivation. Results: Demographic studies showed a predominance of female donors, especially in younger age groups. Most lapsing male donors were 18–35 years old. In this age group, there was a large turnover of male donors. The most common reason for lapsing was simply falling out of habit despite repeated invitations. Other reasons were lack of time, work, travel, new sex partner and change in residence. Adverse events were of less importance. The majority indicated that they would return for donation if they had more time and/or received yet another invitation. Donors lapsing after a single donation would significantly more often donate again, than repeat donors, if they were given information on the use of their blood. Furthermore, single‐time donors found the time spent donating significantly more important. Conclusions: Increased accessibility and repeated invitations are essential for retention of young male donors. Time constraints are important, suggesting improvements in increased availability as well as shortening of visits. Young men also need help integrating blood donation routines into their life.